BPT for Early-Onset Behavior Disorders: Examining the Link Between Treatment Components and Trajectories of Child Internalizing Symptoms. Issue 2 (March 2020) - Rothenberg, W. Andrew; Anton, Margaret T.; Gonzalez, Michelle; Lafko Breslend, Nicole; Forehand, Rex; Khavjou, Olga; Jones, Deborah J.
Behavioral Parent Training (BPT) is the standard of care for early-onset Behavior Disorders (BDs). Preliminary evidence suggests that BPT may also lead to improvement in comorbid symptomatology, particularly internalizing problems, in children with BDs, yet less is currently known about how BPT produces such cascading effects. To begin to address this gap in the literature, trajectory analyses were used to examine the link between treatment components of one mastery-based BPT program, Helping the Noncompliant Child ( HNC ), and child internalizing symptoms over the course of treatment. Findings revealed that parental use of the Attends skill (i.e., parental description of child activity with warmth and enthusiasm) over time was significantly associated with decreases in trajectories of child internalizing symptoms across treatment. Further probing of these effects revealed that parent use of average or above-average levels of Attends across treatment sessions led to significant reductions in child internalizing symptoms by Sessions 7 to 10 of treatment. Consistent with the movement toward a modular approach to the treatment of children, findings highlight the importance of identifying particular BPT skills that can be used in treatment to target multiple comorbid child symptom clusters. Clinical implications and future directions are discussed.